TEACHER PROFESSIONAL DEVELOPMENT IN THE PERSPECTIVE OF TECHNOLOGY PEDAGOGICAL CONTENT KNOWLEDGE THEORETICAL FRAMEWORK - Daniel Ginting; Andini Linarsih (Universitas Tanjungpura, 2022)
Teacher development is an ongoing process through which teachers keep growing with their capabilities. They must be adaptive to the demands of changing times and open to self-professional development. Today, teacher development is challenged to develop not only mastery of science and teaching abilities but also technology. In the perspective of Technology Pedagogical Content Knowledge (TPACK), the meeting of these three competence dimensions can be further divided into seven sub-competencies: technological knowledge, pedagogical knowledge, knowledge of course content, technological pedagogical knowledge, technological content knowledge, pedagogical content knowledge, and technological pedagogical content knowledge. This paper ends with pedagogic implications for teacher professional development that demands high quality and perceived as valuable.